Foundations and future directions in orthodontic treatment planning - Sood, Shweta; Negi, K. S.; Mahajan, Monika; Negi, Susheel (International Journal Of Community Medicine And Public Health, 2025)
Effective management of malocclusion involves precise diagnosis, strategic treatment planning, and careful execution. Diagnosis identifies issues, treatment planning devises solutions, and execution follows the plan. Orthodontic treatment is complex, focusing on esthetics, function, and stability. The goal is to resolve functional issues, align displaced teeth, and improve aesthetics, including correcting overjet and overbite. Success depends on the clinician’s skill, patient cooperation, and managing expectations. Modern orthodontics emphasizes comprehensive outcomes, integrating facial aesthetics, occlusal function, periodontal health, and stability, rather than merely fitting teeth. This article explores the detailed process of orthodontic treatment planning and available options.